Urinary tract infection and antimicrobial resistance profile in patients attending Nemba District Hospital in Rwanda - Bosco, Munyemana Jean; Jonas, Bikorimana; Evelyne, Kantarama; Pauline, Kabanyana (Asian Journal of Medical Sciences, 2020)
Background: About 150 million people worldwide are diagnosed with urinary tract infection (UTI) every year and more than half of women get UTI at least once in their lifetimes. Overuse and misuse of antibiotics have contributed to the growing problem of resistance amongst uropathogenic bacteria making it hard to treat. Aims and Objectives: This study aimed to determine bacteria causing UTIs and their antibiotic resistance profile among patients attending Nemba District Hospital in Rwanda. Materials and Methods: A retrospective study design was used and 267 patient’s data with positive urine culture were reviewed from microbiology laboratory logbooks. Results: In this study, UTI was more frequent in female 180(67.4%) than male 87(32.6%). The most frequently isolated bacteria to cause UTI were Escherichia coli (56.93%) followed by Staphylococcus aureus (28.46%), Proteus spp. (4.49%), Klebsiella spp. (3.75%), Morganella morganii (1.87%), Coagulase Negative Staphylococcus (1.50%), Neisseria gonorrhea (1.12%), Enterobacter spp. (1.12%) and Citrobacter spp. (0.7%). There was a high antimicrobial resistance profile among bacterial isolates. The most commonly used antimicrobial agents including third-generation cephalosporin were resistant to bacterial isolates at a higher rate. Conclusion: These findings suggest continued antimicrobial resistance surveillance and special precautions should be taken for empirical treatment referring to local antimicrobial resistance.